Horticultural, systems-engineering and economic evaluations of short-term plant storage techniques as a labor management tool for vegetable grafting nurseries. - Chieri Kubota; Chao Meng; Young-Jun Son; Myles Lewis; Hans Spalholz; Russell Tronstad (PLoS ONE)
This transdisciplinary study has a three-fold systems approach in evaluating a horticultural technology: 1) horticultural evaluations, 2) economic and resource analyses, and 3) systems engineering analyses, using low temperature storage as an example technology. Vegetable grafting is a technique to produce value-added seedlings but requires labor intensive nursery operations. Low temperature storage of seedlings for a short period of time can reduce peak production, but has not been evaluated at the extent demonstrated in this paper. Seedlings of 22 genotypes of Cucurbitaceae (cucurbit family) and Solanaceae (nightshade family) were evaluated for storability under selected temperatures and photosynthetic photon flux. Storability of Cucurbitaceous seedlings varied between 2 to 4 weeks at 12°C and 13 μmol m-2 s-1. Solanaceous seedlings were generally storable for 4 weeks at 12°C and 13 μmol m-2 s-1, but tomato seedlings could be stored for 4 weeks at 10°C and 5 μmol m-2 s-1. Capital and weekly operational costs of a low temperature storage system with a design that meets environmental requirements were estimated as $671 to $708 per m2 footprint and $0.79 to $2.21 per m2 footprint per week, respectively. Electricity costs per plant was less than 0.1 cents for 2 to 4 weeks of storage. Using a schedule-optimization heuristic and a logistics simulator previously developed for grafting nursery operations, six production scenarios consisting of two crops (tomato or watermelon) and three production peak patterns were examined to evaluate the impact of including low temperature storage. While the overall average costs of grafting labor were not significantly different, maximum labor demand and grafting labor cost during the peak production week were reduced by 31% to 50% and 14% to 30% by using storage, respectively. Therefore, low temperature storage can be an effective means to address the issue of labor management in grafting nurseries.